Bacteroides thetaiotaomicron rough-type lipopolysaccharide: The chemical structure and the immunological activity. (1st December 2022) - Pither, Molly Dorothy; Illiano, Anna; Pagliuca, Chiara; Jacobson, Amy; Mantova, Giuseppe; Stornaiuolo, Alessia; Colicchio, Roberta; Vitiello, Mariateresa; Pinto, Gabriella; Silipo, Alba; Fischbach, Michael A.; Salvatore, Paola; et al.
Abstract: Bacteroides thetaiotaomicron is one of the most extensively studied symbionts of the human gut. Despite its widespread distribution among human populations, still very little is known about the role of its cell envelope in the crosstalk with the immune system. Due to the extraordinary characteristic of B. thetaiotaomicron to express multiple capsular polysaccharides on its surface, research activities focused on defining how these polymers affect immune responses. This resulted in the drawback of neglecting another immunostimulatory cell surface glycoconjugate, the lipopolysaccharide (LPS). By taking advantage of an acapsular mutant of B. thetaiotaomicron, here we describe the characterization of the structure of the rough-type LPS produced by this gut mutualist. This was made up of a mono -phosphorylated and hypoacylated lipid A and of a highly charged core oligosaccharide. In vitro studies revealed a weak ability to engage the MD-2/TLR4 pathway, while it was able to promote TLR2-mediated response. Graphical abstract: Unlabelled Image Highlights: Bacteroides thetaiotaomicron is a Gram-negative bacterium key for the intestinal epithelium and immunological development. It expresses multiple capsular polysaccharides on its surface thus hindering the proper isolation of the lipopolysaccharide (LPS). An acapsular mutant revelead a rough-type LPS (R-LPS) made up of a hypoacylated lipid A and a highly charged oligosaccharide. B. thetaiotaomicron R-LPS showed a weak ability to engage the MD-2/TLR4 pathway, and it activated TLR2-mediated response. A distinct TLR2 and TLR4-mediated cytokine release profile was observed upon cell stimulation with B. thetaiotaomicron R-LPS.